Astrogliosis and compensatory neurogenesis after the first ethanol binge drinking‐like exposure in the adolescent rat. (21st December 2021) - Vilpoux, Catherine; Fouquet, Gregory; Deschamps, Chloe; Lefebvre, Elise; Gosset, Philippe; Antol, Johann; Zabijak, Luciane; Marcq, Ingrid; Naassila, Mickael; Pierrefiche, Olivier
Abstract: Background: Multiple ethanol binge drinking‐like exposures during adolescence in the rat induce neuroinflammation, loss of neurogenesis, and cognitive deficits in adulthood. Interestingly, the first ethanol binge drinking‐like exposure during adolescence also induces short‐ term impairments in cognition and synaptic plasticity in the hippocampus though the cellular mechanisms of these effects are unclear. Here, we sought to determine which of the cellular effects of ethanol might play a role in the disturbances in cognition and synaptic plasticity observed in the adolescent male rat after two binge‐like ethanol exposures. Methods: Using immunochemistry, we measured neurogenesis, neuronal loss, astrogliosis, neuroinflammation, and synaptogenesis in the hippocampus of adolescent rats 48 h after two binge‐like ethanol exposures (3 g/kg, i.p., 9 h apart). We used flow cytometry to analyze activated microglia and identify the TLR4‐expressing cell types. Results: We detected increased hippocampal doublecortin immunoreactivity in the subgranular zone (SGZ) of the dentate gyrus (DG), astrogliosis in the SGZ, and a reduced number of mature neurons in the DG and in CA3, suggesting compensatory neurogenesis. Synaptic density decreased in the stratum oriens of CA1 revealing structural plasticity. There was no change in microglial TLR4 expression or in the number of activated microglia, suggesting a lack of neuroinflammatory processes, although neuronal TLR4 was decreased in CA1 and DG. Conclusions: Our findings demonstrate that the cognitive deficits associated with hippocampal synaptic plasticity alterations that we previously characterized 48 h after the first binge‐like ethanol exposures are associated with hippocampal structural plasticity, astrogliosis, and decreased neuronal TLR4 expression, but not with microglia reactivity. Abstract : The hippocampal cognitive and synaptic plasticity impairments following two binge ethanol exposures in adolescent rat did not induce microglial reactivity but are associated with hippocampal structural plasticity changes, astrogliosis, reduced mature neurons density, while enhancing the number of new immature neurons generated in the subgranular zone of dentate gyrus. Results suggest that two binge‐like ethanol exposures can induce synaptic plasticity disturbances in CA1 by decreasing TLR4 expression in neurons, but not in glial cells.